Analisis Faktor yang mempengaruhi Pembelian Makanan secara Online pada Masa Pandemi Covid-19 menggunakan Metode K-Means Clustering (Studi Kasus: Online Shop Bellyboys.id) - Dicke Rifki Fajrin; Agung Triayudi; Sari Ningsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The presence of the Covid-19 pandemic outbreak makes consumer behavior in shopping began to change. Especially when the enactment of large-scale social restrictions (PSBB) regulations. Providing food service in this place cannot be expected to return. So, the divisions will not think of out of the house just eating in restaurants or eating places. One marketing strategy in the current era offers a message of delivery, this strategy can help remain to comply with regulations that apply during the Pandemic Covid-19. This study aims to obtain the results of the analysis that influences the level of public interest in the purchase of online-based foods, namely by (Food Delivery). This study uses the K-means method and uses the name, age, income, number of orders, order intensity, and satisfaction. This study uses several data collection techniques questionnaire. The subjects of this study are buyers who are members of the Food Delivery Instagram (Bellyboys.id) forum.